In Vitro Inhibition of α-Amylase and α-Glucosidase by Different Parts of Amla Plant (Phyllanthus emblica L) - Novi I. Fauzi; Maria Ulfah; Syarif Hamdani; Saeful Hidayat (Pharmacology and Clinical Pharmacy Research)
Amla plant (Phyllanthus emblica L) has been empirically used to treat diabetes. The aim of this study was to determine the most potential part of amla plant that can be used as α-glucosidase and α-amylase inhibitors. The fruit was subjected to cold extraction method, while the stem underwent soxhlet extraction process. Ethanol was used as solvent for both extracts. In-vitro inhibiton against α-glucosidase and α-amylase enzyme was measured by calculating IC50 of water fractions of stem and fruits. Fruit fraction exhibited the highest percentage of inhibitory activity on α-amylase (IC50=5.68% w/v), while the strongest inhibition against α-glucosidase was shown by leaves fraction (IC50=0.87% w/v). In conclusion, the stem of P. emblica L was potential inhibitor of α-amylase , while the leaves was potential α-glucosidase inhibitor.Keywords: Phyllanthus emblica, α-glucosidase inhibitor, α-amylase inhibitor, fruit, leaves